The Role of Cleaner Production Technology in Indonesia's Food Industry in Improving Product Quality: A Mini Review - Nurul Izzah Aulia; Fatria Resti Haryani; Onne Akbar Nur Ichsan; Syifa' Robbani (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2026)
The food industry in Indonesia faces challenges in improving product quality in line with demands for environmental sustainability and resource efficiency. Clean Production Technology (CPT) is a strategic approach that integrates pollution prevention, energy efficiency, and optimization of raw material use in food production processes. This study aims to briefly review the role and contribution of clean production technology in improving the quality of food industry products in Indonesia. The method used is a literature review of various scientific publications, institutional reports, and policies related to the application of CPP in the food sector. The review results show that the application of clean production technology, such as waste minimization, reuse of by-products, energy and water efficiency, and the application of environmentally friendly process technology, contributes positively to improving product quality, food safety, and quality consistency. In addition, TPB also supports the improvement of the food industry's competitiveness through reduced production costs and an improved corporate environmental image. However, the implementation of TPB in Indonesia still faces obstacles in the form of technological limitations, initial investment, and low awareness and capacity of human resources. Therefore, synergy between industry players, government, and academics is needed to strengthen the sustainable adoption of clean production technology. The results of this study are expected to be an initial reference in the development of policies and strategies for the application of TPB in the national food industry. Keywords: Resource efficiency, food industry, environmental sustainability, product quality, clean production technology